2007
DOI: 10.1136/sti.2006.024372
|View full text |Cite
|
Sign up to set email alerts
|

The use of serological titres of IgA and IgG in (early) discrimination between rectal infection with non-lymphogranuloma venereum and lymphogranuloma venereum serovars of Chlamydia trachomatis

Abstract: An increased IgA antibody response and the age of the infected individual are of possible diagnostic value for (early) detection of LGV proctitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…As published previously, and also mentioned in the article by van der Snoek et al ,4 a considerable number of the patients with LGV proctitis in the present epidemic are asymptomatic 2 5. In a retrospective case–control study2 we found that only 47% of LGV cases had signs of proctitis (mucous membrane abnormalities) upon proctoscopic examination.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…As published previously, and also mentioned in the article by van der Snoek et al ,4 a considerable number of the patients with LGV proctitis in the present epidemic are asymptomatic 2 5. In a retrospective case–control study2 we found that only 47% of LGV cases had signs of proctitis (mucous membrane abnormalities) upon proctoscopic examination.…”
supporting
confidence: 77%
“…In a recent interesting study, van der Snoek et al 4 concluded that an elevated Chlamydia trachomatis IgA antibody response and the age of the infected individual are of possible diagnostic value for the early detection of LGV proctitis. Based on their study of 24 MSM with L2 proctitis and 15 MSM with rectal C. trachomatis (non-LGV) infection, the authors suggest that the association between LGV L2 and significantly higher titres of IgA and IgG are caused by more invasive and more chronic inflammation of the proctum caused by the LGV biovar.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases classified as possible or probable LGV could be non-LGV associated C. trachomatis serovars. Nevertheless, invasive titers, used as a diagnostic criterion in our study, were found of possible diagnostic value for LGV proctitis in another study (Van der Snoek et al 2008). An LGV outbreak among MSM has already been observed in at least 11 European countries (Timen et al 2008).…”
Section: Discussionmentioning
confidence: 84%
“…IgA anti-MOMP antibodies) in a patient with a clinical syndrome suggestive of LGV supports the diagnosis. 21,22 Nonetheless, a low titre does not exclude LGV, nor does a high titre in a patient without LGV symptomatology confirm LGV infection. 10,11 (III, B) The identification of rectal polymorphonuclear leucocytes from rectal swabs is predictive of LGV proctitis, especially in HIV-positive MSM, with levels greater than 10 cells per high power field.…”
Section: Clinical Featuresmentioning
confidence: 99%